Cutaneous larva migrans: an unusual souvenir from a Scottish holiday. (23rd November 2021) - Paget, S.; Fernandez, C.; Zaheri, S.
Abstract : Cutaneous larva migrans acquired in western Scotland. A reminder that with a warming climate, conditions conventionally restricted to the tropics may be contracted in the British Isles in the absence of foreign travel.